Chinese Medicine on the Move into Central Europe: A Contribution to the Debate on Correlativity and Decentering STS. Issue 1 (1st March 2018) - Stöckelová, Tereza; Klepal, Jaroslav
Abstract: Contributing to the ongoing debate on decentering science, technology, and society (STS) from Western contexts, this article elaborates on and reconsiders Wen-yuan Lin and John Law's proposal for correlative STS ("A Correlative STS" 2014). Like them, we empirically draw on Chinese medicine (CM) and its relation to biomedicine, but we explore the modes by which CM was enacted in the historical, political, and sociomaterial settings of socialist and postsocialist Central Europe. We show that not only specific correlations but also correlativity itself—as the ontological stance of the actors—are situated and can shift. Our argument regarding STS is twofold. First, while Lin and Law argue that STS needs to develop an appropriate mode of betrayal when translating across ontological differences from a source language to a destination language (Western analytics), we show that in our case an ethnographer cannot find any single source language. Consequently, we argue that STS should study actors' modes and moves of betrayal and their doing ontology as an open process. Second, unlike Lin and Law, who postulate the Chinese mode of international as "subtle" and "minimalist" and an alternative to the Western mode (Lin and Law 2013 ), we argue that with the rise of China and the changing world political economy, STS needs to be more attentive to dominating expansions that come from non-Western locations as much as from the West.